Adaptation of dairy cattle towards climate change by improved housing and management - DAS, S K; SINGH, N P (The Indian Journal of Animal Sciences, 2014)
Effect of change of different micro-environmental parameters had significant influence on daily and monthly milk yield of cows. Influence was more pronounced on crossbred cows than that on indigenous cows. Modification in housing and arrangement of cooling in cattle shed had reduced the heat stress and thereby decreased the milk drop due to change of microenvironment.